Effect of silk taro flour substitution (Colocasia esculenta L. Schott) on physical properties, organoleptic properties, and antioxidant activity in steamed brownies - Yahriz Eka Septianto; Noor Tifauzah; Nugraheni Tri Lestari; Susilo Wirawan (University of Darussalam Gontor, 2022)
Background : Silk taro plant is one of the varieties of minor tubers plants used as food crops. The content of vitamin C as a source of antioxidant substances silk tarogood to strengthen the immune systemand to prevent the formation of free radicals in the body. Silk taro flour has the potential to be developed into a variety of food products, one of which was steamed brownies in this study. Objectives: Known the influence of variations of silk taro flour mixture on physical properties, organoleptic properties, and antioxidant activity in steamed brownies. Method: This type ofresearch is a pure experiment with Simple Randomized Design (SRD), using 4 (four) treatments, 2 (two) units of trial, and 2 (two) replication. Physical properties data are analyzed descriptively, organoleptic properties data are analyzed with Kruskal-Wallis Test while antioxidant activity data was analyzed descriptively. Results: Based on the physical properties of brownies, the more the addition of silk taro flour the, darker the color and the harder the texture. The more the addition of silk taro flour aroma, the more fragrant typical silk taro, while the taste had no significant difference that wassweet and had the higher antioxidant activity. Conclusion: Silk taro flour brownies favored by panelists and can be developed based on physical properties, organoleptic. properties and antioxidant activity was the brownies with 50% composite of silk taro flour.Keywords : antioxidant activity, brownies, organoleptic properties, physical properties, silk taro flour AbstrakLatar Belakang : Talas sutera merupakan salah satu varietas umbi-umbian minor yang digunakan sebagai tanaman pangan. Kandungan vitamin C sebagai sumber zat antioksidan talas sutera baik untuk memperkuat daya tahan tubuh dan mencegah terbentuknya radikal bebas dalam tubuh. Tepung talas sutera berpotensi untuk dikembangkan menjadi berbagai produk makanan, salah satunya brownies kukus pada penelitian ini. Tujuan : Tujuan penelitian adalah mengetahui pengaruh variasi campuran tepung talas sutera terhadap sifat fisik, sifat organoleptik, dan aktivitas antioksidan pada brownies kukus. Metode : Jenis penelitian ini adalah eksperimen murni dengan Rancangan Acak Sederhana (RAS), menggunakan 4 (empat) perlakuan dalam bentuk brownies, 2 (dua) unit coba, dan 2 (dua) kali ulangan. Data sifat fisik dianalisis secara deskriptif, data sifat organoleptik dianalisis dengan Uji Kruskal-Wallis sedangkan data aktivitas antioksidan dianalisis secara deskriptif. Hasil : Berdasarkan sifat fisik brownies, semakin banyak penambahan tepung talas sutera warna semakin cokelat tua dan tekstur semakin keras. Semakin banyak penambahan tepung talas sutera aroma semakin harum khas talas suterayaitu sedikit langu harum sedangkan rasa tidak ada perbedaan signifikan yaitu manis dan aktivitas antioksidan yang dihasilkan semakin tinggi. Kesimpulan : Brownies tepung talas sutera yang disukai panelis serta dapat dikembangkan berdasarkan sifat fisik, sifat organoleptik dan aktivitas antioksidan adalah brownies dengan variasi pencampuran tepung talas sutera 50%.